Misregulation of Alternative Splicing Causes Pathogenesis in Myotonic Dystrophy - Muge Kuyumcu-Martinez, N. (2006)
Myotonic dystrophy (DM), the most common form of adult onset muscular dystrophy, affects skeletal muscle, heart, and the central nervous system (CNS). Mortality results primarily from muscle wasting and cardiac arrhythmias. There are two forms of the disease: DM 1 and DM 2. DM 1, which constitutes 98% of cases, is caused by a CTG expansion in the 3′ untranslated region (UTR) of the DMPK gene. DM 2 is caused by a CCTG expansion in the first intron of the ZNF9 gene. RNA containing CUG- or CCUG-expanded repeats are transcribed but are retained in the nucleus in foci. Disease pathogenesis results primarily from a gain of function of the expanded RNAs, which alter developmentally regulated alternative splicing as well as pathways of muscle differentiation. The toxic RNA has been implicated in sequestration of splicing regulators and transcription factors thereby causing specific symptoms of the disease. Here we review the proposed mechanisms for the toxic effects of the expanded repeats and discuss the molecular mechanisms of splicing misregulation and disease pathogenesis.